Professional ASP. NET MVC 5 / Jon Galloway...[et al.] - Galloway, Jon
MVC 5 is the newest update to the popular Microsoft technology that enables you to build dynamic, data-driven websites. Like previous versions, this guide shows you step-by-step techniques on using MVC to best advantage, with plenty of practical tutorials to illustrate the concepts. It covers controllers, views, and models; forms and HTML helpers; data annotation and validation; membership, authorization, and security.